2009
DOI: 10.1603/008.102.0612
|View full text |Cite
|
Sign up to set email alerts
|

Review of North American Species of the GenusOnychiurus(Collembola: Onychiuridae), with a Description of Four New Species from Caves

Abstract: The history of the genus Onychiurus is discussed. Four new Onychiurus species are described from North American caves: steinmanni and nathanieli from Colorado, reluctoides from Indiana, and furcisetosus from Virginia. Onychiurus reluctus Christiansen, 1961 is redescribed. A key for all of the known North American species is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Most individuals of O. pipistrellae n. sp. will key out to O. steinmanni Pomorski, Furgol, andChristiansen, 2009 in Pomorski et al (2009), but the new species is easily distinguished from O. steinmanni by the number of pseudocelli on Th. 2-3, the number of setae on ventral tube, the number of PAO vesicles, and, apparently, the number of proximal setae on the labial palp.…”
Section: Vitronura Giselae Gisin 1950 -Tx In? Locality: Wanda's Watementioning
confidence: 96%
See 2 more Smart Citations
“…Most individuals of O. pipistrellae n. sp. will key out to O. steinmanni Pomorski, Furgol, andChristiansen, 2009 in Pomorski et al (2009), but the new species is easily distinguished from O. steinmanni by the number of pseudocelli on Th. 2-3, the number of setae on ventral tube, the number of PAO vesicles, and, apparently, the number of proximal setae on the labial palp.…”
Section: Vitronura Giselae Gisin 1950 -Tx In? Locality: Wanda's Watementioning
confidence: 96%
“…The populations from Bat Sump and Stemler caves were previously sampled and identify as O. reluctus (Lewis et al, 2003). However, the redescription of O. reluctus by Pomorski et al (2009) This species is commonly found on surface leaf litter across temperate and tropical regions of the world (Potapov, 2001;Mari Mutt and Bellinger, 1990), and in Illinois it was previously known from Champaign County. This appears to be the first record for this species from Illinois caves.…”
Section: Vitronura Giselae Gisin 1950 -Tx In? Locality: Wanda's Watementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, O. wilchi was described and illustrated as having 18-20 vesicles in the PAO, whereas none of the Onychiurus spp. in Pomorski et al (2009) has more than 17 vesicles in the PAO. Thus, it appears that O. wilchi may be a recognizable species and that it is premature to synonymize any of these species.…”
mentioning
confidence: 98%
“…There are approximately 60 species of cave Collembola known from U.S. caves and he described nearly 50 of them! During the course of his career, he described species from all the major genera of Collembola occupy-ing North American caves-Onychiurus (Pomorski et al 2009), Pseudosinella [Christiansen 1960b[Christiansen , 1983Christiansen and Luther 1986;Christiansen and Moberg 1988;Christiansen and Bellinger 1996b), Pygmarrhopalites (Christiansen 1966;Christiansen and Bellinger 1996a;Zeppelini and Christiansen 2003), Sinella (Christiansen 1960c), and Tomocerus (Christiansen 1964a). …”
mentioning
confidence: 99%